2008
DOI: 10.1002/jso.20970
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors and leiomyosarcomas

Abstract: Only recently has gastrointestinal stromal tumor (GIST) been recognized as the most frequent GI mesenchymal neoplasm. Prior to the use of KIT staining, most GI stromal tumors were identified as leiomyosarcoma (LMS). For primary GIST, surgery remains the principal treatment and adjuvant imatinib may improve outcomes. Multimodality therapy may also be effective in patients with metastatic GIST. In this review, we summarize the epidemiology, clinicopathologic features, natural history, and clinical management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 92 publications
(108 reference statements)
1
102
1
2
Order By: Relevance
“…11 KIT mutations in GISTs result in constitutive activation of receptor tyrosine kinases independent of ligand binding. 4,11,26 The most common mutations are in the juxtamembrane domain (exon 11), 4,7,16,17,26,28 a protein sequence that is highly conserved, with 100% homology between humans and dogs. 4 Similar mutations in KIT are demonstrated in dogs and humans, 4 suggesting that canine tumors with KIT mutations may behave similarly and respond in the same way to targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 KIT mutations in GISTs result in constitutive activation of receptor tyrosine kinases independent of ligand binding. 4,11,26 The most common mutations are in the juxtamembrane domain (exon 11), 4,7,16,17,26,28 a protein sequence that is highly conserved, with 100% homology between humans and dogs. 4 Similar mutations in KIT are demonstrated in dogs and humans, 4 suggesting that canine tumors with KIT mutations may behave similarly and respond in the same way to targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the neoplasm may be helpful in these cases, as some neoplasms in human cases have KIT mutations without exhibiting KIT immunoreactivity. 7,28 No statistical conclusions could be made regarding associations between survival and various gross features, microscopic features, or proliferation markers due to insufficient follow-up data for statistical analysis. A recent study reported that tumor diameter was an important prognostic indicator and mitotic count was a less significant indicator in cases of canine GISTs compared with cases of human GISTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These tumors rarely metastasize. Their malignant potential is determined by size, location, mitotic rate, and degree of local invasiveness [ 27 ] (Fig. 12.7 ).…”
Section: Mark the Correct Statement Regarding Hypertrophic Pyloric Stmentioning
confidence: 99%